26.0k views
1 vote
Solve: 6(y-5) = 2(10 + 3y)

User Kbang
by
5.4k points

2 Answers

3 votes
Simplifying
6[y + -5] = 2(10 + 3y)

Reorder the terms:
6[-5 + y] = 2(10 + 3y)
[-5 * 6 + y * 6] = 2(10 + 3y)
[-30 + 6y] = 2(10 + 3y)
-30 + 6y = (10 * 2 + 3y * 2)
-30 + 6y = (20 + 6y)

Add '-6y' to each side of the equation.
-30 + 6y + -6y = 20 + 6y + -6y

Combine like terms: 6y + -6y = 0
-30 + 0 = 20 + 6y + -6y
-30 = 20 + 6y + -6y

Combine like terms: 6y + -6y = 0
-30 = 20 + 0
-30 = 20

Solving
-30 = 20

Couldn't find a variable to solve for.

no solution
User Erogol
by
6.4k points
3 votes

Answer:

no solution

Explanation:

simplifying

6(y + -5) = 2(10 + 3y)

reorder the terms:

6(-5 + y) = 2(10 + 3y)

(-5 * 6 + y * 6) = 2(10 + 3y)

(-30 + 6y) = 2(10 + 3y)

-30 + 6y = (10 * 2 + 3y * 2)

-30 + 6y = (20 + 6y)

add '-6y' to each side of the equation.

-30 + 6y + -6y = 20 + 6y + -6y

combine like terms: 6y + -6y = 0

-30 + 0 = 20 + 6y + -6y

-30 = 20 + 6y + -6y

combine like terms: 6y + -6y = 0

-30 = 20 + 0

-30 = 20

solving for:

-30 = 20

the left and right sides are not equal, so there isn't any solution!

User Yakalent
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.